2006
DOI: 10.1055/s-2006-948306
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Deficiency Impacts the Pancreatic Th1/Th2 Cytokine Profile Following Multiple Low Dose Streptozotocin-Induced Diabetes

Abstract: Osteopontin (OPN) is a phosphorylated acidic glycoprotein that causes chemotaxis of macrophages and downregulation of nitric oxide synthesis. OPN has been shown to be involved in the pathogenesis of autoimmune diseases. Here, we tested the hypothesis that increased expression of pancreatic OPN in experimental diabetes has a protective role. The immune response phenotype associated with the induction of diabetes was evaluated in male OPN knockout (KO) and wild type (WT) mice. Multiple low dose streptozotocin (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…18 Using an OPN knockout model, we showed that OPN is essential for polarizing the islet cytokine immune response towards the protective Th2 profile. 19 We also demonstrated that OPN regulates NO signaling in the islets and b-cells via an RGD-mediated feedback regulation of IL-1b-induced nuclear factor-kB (NFkB) activation with consequent downregulation of induced nitric oxide synthase activity and increased b-cell survival. 20 In this study, we used different age groups of the NOD mice, which spontaneously develop a form of type I diabetes and shares many features of the human disease.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…18 Using an OPN knockout model, we showed that OPN is essential for polarizing the islet cytokine immune response towards the protective Th2 profile. 19 We also demonstrated that OPN regulates NO signaling in the islets and b-cells via an RGD-mediated feedback regulation of IL-1b-induced nuclear factor-kB (NFkB) activation with consequent downregulation of induced nitric oxide synthase activity and increased b-cell survival. 20 In this study, we used different age groups of the NOD mice, which spontaneously develop a form of type I diabetes and shares many features of the human disease.…”
mentioning
confidence: 78%
“…Based upon previous data supporting the protective and pro survival role of OPN in various tissues 10,11,36 and in the pancreatic islets and b-cells, 18,19,20 we propose that the high levels of islet OPN during the early stages of autoimmune diabetes might isolated from pancreata, islets or b-cells using Trizol reagent (Life Technologies, Gaitherburg, MD), according to the manufacturer's protocol. RNAs were quantified and input amounts were optimized for each amplicon.…”
Section: Rna Extraction and Real Time Reverse Transcription Polymerasmentioning
confidence: 99%
“…Furthermore, it has been well documented that low level inflammation associated with the early stages of T2D leads to upregulation of OPN mRNA and iOPN protein expression in pancreatic islets [42, 44, 47, 53]. Elevation of iOPN serves a protective role in pancreatic islets where it acts as a negative feedback regulator of induced NO synthase (iNOS) and as a promoter of a protective Th2 immune response [42, 44, 47, 54]. Interestingly, TALK-1 channels are activated by NO.…”
Section: Discussionmentioning
confidence: 99%